Дырка от бублика: [повесть] / Галина Куликова - Куликова Галина Михайловна (Иронический детектив, 2004)
Экземпляры: Ф. 2 (20200114) / Инвентарный номер: 47483 / Цена: 15.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: К 90 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44